1997
DOI: 10.1210/endo.138.8.5306
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Murine Gonadotropin-Releasing Hormone Receptor-Luciferase Fusion Gene in Transgenic Mice Is Diminished by Immunoneutralization of Gonadotropin-Releasing Hormone

Abstract: A line of transgenic mice harboring a fusion gene consisting of 1900 bp of proximal 5'-flanking region from the murine GnRH receptor gene linked to the complementary DNA encoding luciferase was established to determine whether this promoter can direct tissue-specific expression in vivo and serve as a model for identifying the molecular mechanisms underlying hormonal regulation of this gene. Of 10 tissues screened, luciferase was detected predominantly in pituitary gland, but also in brain and testis. To assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…In contrast to GnRH, antide had no effect on the fraction of mobile receptors. Consistent with this, we have found that the promoter of the GnRHR gene is hormonally regulated in transgenic mice (16). Furthermore, fluorescence photobleaching recovery analysis of the GnRHR-green fluorescent protein fusion reveals fundamental differences in the membrane dynamics of the GnRHR induced by the binding of an agonist vs. that induced by the binding of an antagonist.…”
supporting
confidence: 74%
“…In contrast to GnRH, antide had no effect on the fraction of mobile receptors. Consistent with this, we have found that the promoter of the GnRHR gene is hormonally regulated in transgenic mice (16). Furthermore, fluorescence photobleaching recovery analysis of the GnRHR-green fluorescent protein fusion reveals fundamental differences in the membrane dynamics of the GnRHR induced by the binding of an agonist vs. that induced by the binding of an antagonist.…”
supporting
confidence: 74%
“…This syndrome arises as a failure of GnRH neurons to migrate from the olfactory placode to the hypothalamus correctly during embryogenesis resulting in decreased levels of GnRH and subsequent gonadotropins [810]. In addition to various naturally occurring mutations in humans, several experimental models also underscore the critical role of GnRH/GnRH receptor (GnRHR) signaling including mutation of the GnRHR gene [11, 12], genetic ablation of gonadotropes [13], immunoneutralization of GnRH [14, 15], and animal models of hypothalamic-pituitary disconnection [16, 17]. Thus, fertility is not only dependent on proper GnRH production and release from the hypothalamus but also its subsequent binding to high affinity GnRHR on pituitary gonadotropes and the coordination of these events is of universal importance in controlling reproduction in mammals.…”
Section: Introductionmentioning
confidence: 99%
“…The first transgenic studies were performed using the luciferase reporter gene under the control of the mouse (1.9 kb) and ovine (9 or 2.7 kb) 5′ flanking regions of Gnrhr . One major contribution of these models was to quantify promoter activity with high sensitivity in homogenates from several organs and, subsequently, to compare this activity in pituitary and extra‐pituitary sites . Thus, the mouse Gnrhr promoter induced strong luciferase activity (adjusted for protein content) in the pituitary gland as expected and, to a lesser extent, in the whole brain, in which luciferase activity was estimated to be approximately 10% of that in the pituitary .…”
Section: Species Specificities In the Mechanisms Regulating Gnrhr Expmentioning
confidence: 91%
“…Thus, the mouse Gnrhr promoter induced strong luciferase activity (adjusted for protein content) in the pituitary gland as expected and, to a lesser extent, in the whole brain, in which luciferase activity was estimated to be approximately 10% of that in the pituitary . In addition, this promoter led to weak and variable luciferase expression in the testis, corresponding to 1% of the estimated level of expression in the pituitary . In our laboratory, we recently investigated Gnrhr expression in mouse testis but were unable to detect transcripts using conventional real‐time RT‐PCR .…”
Section: Species Specificities In the Mechanisms Regulating Gnrhr Expmentioning
confidence: 99%
See 1 more Smart Citation